Spiritualities of the Body: Yoga, Spirituality and Health in Italy - Placido, Matteo Di (Religions, 2023)
Modern postural yoga, a body–mind practice developed in the last hundred and fifty years at the intersection of therapeutic, fitness and spiritual logics, is experiencing an unprecedented worldwide diffusion, including in Italy. This article, relying on discourse analysis of three yoga manuals and twenty-seven biographical interviews of yoga practitioners, aims at exploring yoga’s positioning in the Italian context, with particular attention paid to its practical–discursive construction as a contemporary form of spiritualities of the body, defined as spiritualities oriented towards practitioners’ ‘unmediated’ relationship with the sacred and the cultivation of well-being through “body work”. More specifically, the article investigates the “cultural pragmatics” of a selection of Italian yoga manuals, scripted performances (regarding health and spirituality) capable of directly influencing and impacting practitioners’ “social imaginaries” of yoga in their everyday practice. In so doing, it also contributes to discussing the circular and reciprocal relationship between “discourses” and “practices” within specific contexts of practice, such as yoga classes and teacher training courses. The article concludes by emphasizing which conceptualizations of health and spirituality are promoted, transmitted and in turn embodied during yoga practice, the role of health discourses and pedagogies in the professionalization of yoga and the growing practical–discursive construction of the yoga teacher as a spiritual director and health expert.